Ben pao de dai er niu - Huang, Beijia 1955- (Huang Bei jia qing qing xiao shuo xi lie, 2021)
Large tracts of bright and charming pink grass have made Hongcaoba a new popular attraction for rural tourism. However, Dai Erniu's father, is immersed in his "grass skiing" experiment and turns a blind eye to the opportunity to get rich. Thin and weak Dai Erniu becomes the only supporter of his father's grand ideal…